STYLISTIC ASPECT OF TRANSLATING INCOMPLETE SENTENCES IN THE MAP AND THE TERRITORY BY M. HOUELLEBECQ INTO THE UKRAINIAN LANGUAGE - Filonenko, Nataliia (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The paper analyses the syntactic and punctuation features of incomplete sentences in view of polyphony and the narrative perspective of literary prose text, outlines a stylistic plan for structuring sentences in the plane of author’s intention, and also highlights the issues of its adequate transfer in translating and searching for syntactic equivalents of the type of sentences being studied. The choice of syntactic constructions of a certain type for expressing the author’s intention and their stylistic potential forms an additional pragmatic meaning. Special authoring use of stylistic resources of syntax and punctuation, a specific way of segmentation and structuring of literary prose text, prompts an interpreter to solve problems of translation equivalence associated with conservation of author’s style when translating texts of modern French literary prose. This translation task causes the aspiration to use such syntactical units in the translation text that are identical or similar to the syntactical units of the original text, which confirms to a certain extent the invariance of the syntactic values of the source and the final texts. Incomplete sentences are often represented by ellipses, parcels, and abbreviated sentences. They are typical syntactical units of the very artistic prose text and are widely used by modern French authors, especially in the spoken language of characters, namely in dialogues. In a constructive focus these units are extremely diverse, expressively effective and represent the field of the author’s stylistic game. Given the syntactic functions of parts of the language, the composition of incomplete sentences cannot be reliably determined, which gives rise to the possibility of their interpretive variability. A simple comparison of the analysed syntactical units of the source text and the corresponding translation fragments indicates that the translator follows the task of maintaining the incomplete sentence syntax framework using syntactic equivalents. _____________ References • Belousov K. Y. Activity-ontological concept of text formation. Dokt, Diss. Orenburg, 2005. 374 p. • Gak V. G. Theoretical grammar of the French language. – M. : Dobrosvet, 2000. – 839 p. • Nikolina N. A. Philological analysis of the text. – M. : Izdatelskij centr "Akademiya", 2003. – 256 p. • Filonenko N. G. Syntactic Organisation of the Contemporary French Fictional Prose Texts: Cognitive, Lingual and Synergetic Aspects. Dokt, Diss. Kyiv, 2016 – 504 p. • Grevisse M. Le bon usage. Grammaire française avec des remarques sur la langue française d’aujourd’hui.– P., 2008. – 1156 p. • Houellebecq M. La carte et le territoire. – Flammarion, 2010. – 427 р. • Houellebecq M. The Map and the Territory translated by L.G.Kononovich. – Harkiv : Folio, 2013 (2012). – 347 p.